Numerical modeling of the Ria de Aveiro plume: a preliminary study - Mendes, Renato Paulo dos Santos (2012)
The Ria de Aveiro is one of the largest shallow water estuarine systems of Portugal. It is located on the northern coast of Portugal and it is characterized by a large number of narrow channels and intertidal areas, subject to an enormous natural and anthropic stress. Therefore, it becomes essential the numerical study of its hydrodynamics. In recent years, several studies regarding numerical modeling of the lagoon have been performed, but none of them had its focus on the dynamics of the estuarine plume of the lagoon to the Atlantic Ocean. This buoyant plume injects less dense water which penetrates onto the coastal zone. Then, it is generated an offshore movement in the surface layer during the ebbing. The structure of the estuarine plume is usually characterized by a buoyant bulge, propagating radially. Their shape may vary due to several factors: differences in the ocean and estuarine discharge water properties; bathymetric variations; and meteorological factors, in particular the wind direction and intensity. The main objective of this study is to perform a preliminary study of the Ria de Aveiro estuarine plume, as well as its qualitative assessment during extreme river discharges conditions (maximum and minimum) and a typical value to January. The baroclinic finite volume numerical model, Mohid, was implemented to the Ria de Aveiro in a 2D mode, in order to quantify the flow (and its properties) that the lagoon injects into the ocean. The model was calibrated and validated (hydrodynamic and transport processes), and the RMS errors and Skill values reflect the good performance of the model. After the three different river discharges scenarios were simulated. Then, based on the nested models methodology were created two other coastal domains. The first (2D mode) covers the entire Iberian Peninsula and surrounding areas, with a variable resolution (0.02º-0.04º), and it was forced by a global tidal model in its lateral boundaries. The second (3D mode), with more resolution (0.01º) is located between Figueira da Foz and Caminha, and includes the coastal area of the plume propagation. The hourly lagoon discharge, previously calculated through the model runs of Ria de Aveiro, was imposed in the lagoon mouth location, in order to allow the study of the estuarine plume dynamics. The forecast results for the coastal zone adjacent to Ria de Aveiro show similar patterns comparing to satellite images obtained by the TM sensor-Landsat7, at the surface, to a day of intense river inflow. In the highest flow simulation, the plume expands to about 25 km, creating a bulge in front of the lagoon mouth. Then, it is advected to the right (Coriolis effect) and after the establishment of the geostrophic balance is extended along the northern coast. The typical inflow results have similar patterns, but less pronounced. The simulations for the minimum inflow rate show that the plume is almost nonexistent. In this scenario, the salinity differences are minimal (<0.5 psu) and the thermal gradients tend to control the estuarine plume establishment. This approach could be a starting point for further studies and improvements in the monitoring of the dynamics of Ria de Aveiro plume.